2020
DOI: 10.21873/invivo.12102
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Expression of H2S-Producing Enzyme in Human Renal Cell Carcinoma Specimens: Potential Avenue for Future Therapeutics

Abstract: Background: Renal cell carcinoma (RCC) is the most common cancer of the kidney. The most common histotype is clear-cell (cc) RCC. Hydrogen sulfide (H 2 S) is an angiogenic and anti-apoptotic gasotransmitter that is elevated under pseudohypoxic conditions. H 2 S is endogenously produced by three enzymes: Cystathionine γ-lyase (CSE), cystathionine βsynthase (CBS), and 3-mercaptopyruvate sulfurtransferase (MPST). Seeing as increased expression of these enzymes has been observed in other human cancer types, this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Renal oncocytoma, renal urothelial carcinoma, and renal clear cell carcinoma clinical samples also showed increased CBS expression, as evidenced by immunohistochemical analysis [ 72 , 73 ]. In an earlier report, in renal clear cell carcinoma samples a clear increase in CBS expression was seen as a function of increasing tumor stage; Fuhrman IV samples had over 3-times more CBS than Fuhrman I stage samples [ 72 ].…”
Section: Cbs Expression In Various Human Cancers: Correlation With Cl...mentioning
confidence: 99%
See 1 more Smart Citation
“…Renal oncocytoma, renal urothelial carcinoma, and renal clear cell carcinoma clinical samples also showed increased CBS expression, as evidenced by immunohistochemical analysis [ 72 , 73 ]. In an earlier report, in renal clear cell carcinoma samples a clear increase in CBS expression was seen as a function of increasing tumor stage; Fuhrman IV samples had over 3-times more CBS than Fuhrman I stage samples [ 72 ].…”
Section: Cbs Expression In Various Human Cancers: Correlation With Cl...mentioning
confidence: 99%
“…In an earlier report, in renal clear cell carcinoma samples a clear increase in CBS expression was seen as a function of increasing tumor stage; Fuhrman IV samples had over 3-times more CBS than Fuhrman I stage samples [ 72 ]. However, in a subsequent report, CBS enzyme expression patterns in renal clear cell carcinoma versus normal tissue did not correlate with nuclear grade, stage, histological type or cancer recurrence/metastasis [ 73 ]. According to analysis of the renal clear cell adenocarcinoma; KIRC Dataset, the level of CBS expression does not affect clinical prognosis [ 55 ].…”
Section: Cbs Expression In Various Human Cancers: Correlation With Cl...mentioning
confidence: 99%
“…H 2 S is synthesized by three enzymes, cystathione β-synthase, CSE, and 3-mercaptopyruvate sulfurtransferase , (8). H 2 S and one or more of the enzymes that synthesize it are increased in several common human malignancies, including prostate, breast, colon, oral squamous cell, and renal cell carcinomas (9)(10)(11)(12)(15)(16)(17). A role for H 2 S or the enzymes that synthesize it in testicular cancer has not been previously examined.…”
Section: Discussionmentioning
confidence: 99%
“…Cystathionine gamma-lyase (CSE) catalyzes hydrogen sulfide (H 2 S) synthesis by the conversion of cystathionine to L-cysteine, yielding pyruvate, ammonia, and H 2 S (8). CSE is increased in several human malignancies (9)(10)(11)(12). Interestingly, CSE promotes tumor metastases in breast and prostatic cancer (9, 10).…”
mentioning
confidence: 99%
“…In HUVECs, the high concentration (50 ng/ml) of TNFα and a longer treatment duration (6 h) downregulated CSE expression, which may reduce endogenous H 2 S production and induce the inhibition of vascular smooth muscle relaxation (38) resulting in reduced local blood flow (39). This may lead to the chronic insufficiency of blood supply to local tumor tissue, resulting in the induction of apoptosis (19) and in the prevention of tumor recurrence, this suggests a potential therapeutic target for tumor (40). These results demonstrated that the DNA sequence, GGGACATTCC, on the CSE gene promoter was directly associated with the transcriptional regulation of the CSE gene in mammalian cells treated with TNFα.…”
Section: Discussionmentioning
confidence: 99%